An all-optical excitonic switch operated in the liquid and solid phases - Kellis, Donald L.; Sarter, Christopher; Cannon, Brittany L.; Davis, Paul H.; Graugnard, Elton; Lee, Jeunghoon; Pensack, Ryan D.; Kolmar, Theresa; Jäschke, Andres; Yurke, Bernard; Knowlton, William B. (ACS nano, 2019)
The excitonic circuitry found in photosynthetic organisms suggests an alternative to electronic circuits, but the assembly of optically active molecules to fabricate even simple excitonic devices has been hampered by the limited availability of suitable molecular scale assembly technologies. Here we have designed and operated a hybrid all-optical excitonic switch comprised of donor/acceptor chromophores and photochromic nucleotide modulators assembled with nanometer scale precision using DNA nanotechnology. The all-optical excitonic switch was operated successfully in both liquid and solid phases, exhibiting high ON/OFF switching contrast with no apparent cyclic fatigue through nearly 200 cycles. These findings, combined with the switch’s small footprint and volume, estimated low energy requirement, and potential ability to switch at speeds in the 10s of picoseconds, establish a prospective pathway forward for all-optical excitonic circuits.
Gesehen am 11.07.2019